2004
DOI: 10.1111/j.1440-0960.2004.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell basal cell carcinoma

Abstract: A 69-year-old woman presented with a 2-year history of a slowly growing tumour on the nose. The clinical diagnosis was basal cell carcinoma (BCC) and a complete excision was performed. Histologically, the tumour had the general features of a BCC but with sheets and nests of cells with granular cytoplasmic changes in the centre of the lesion. A pathological diagnosis of granular cell BCC was made. On immunohistochemical examination, the tumour cells were Ber-EP4, cytokeratin AE1/AE3 and cytokeratin CAM 5.2 posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…The vesicles responsible for morphologic change of the cytoplasm had ultrastructural features of lysosomes and represent either true lysosomes or infoldings of the cytoplasmic membrane subsequently phagocytosed and digested by lysosomes . Expression of CD68 (KP1 clone), a glycoprotein epitope associated with lysosomal membranes, was documented by immunohistochemical studies in one previously reported tumor…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The vesicles responsible for morphologic change of the cytoplasm had ultrastructural features of lysosomes and represent either true lysosomes or infoldings of the cytoplasmic membrane subsequently phagocytosed and digested by lysosomes . Expression of CD68 (KP1 clone), a glycoprotein epitope associated with lysosomal membranes, was documented by immunohistochemical studies in one previously reported tumor…”
Section: Discussionmentioning
confidence: 94%
“…The prototypical dermal neoplasm with granular cell features is the so‐called granular cell tumor , which because of its expression of S100 protein is thought to be of Schwann cell lineage . Granular cell features, however, have been reported in many different tumor types, including leiomyoma, leiomyosarcoma, atypical fibroxanthoma, angiofibroma, dermatofibroma, dermatofibrosarcoma protuberans, melanoma, non‐neural granular cell tumor (primitive polypoid granular cell tumor), angiosarcoma and BCC …”
Section: Discussionmentioning
confidence: 99%
“…Reactivity for these lysosome-associated immunohistochemical markers has also been reported in other granular-cell tumours [19,20,21]. Monoclonal antibody KP1 recognizes an epitope of CD68 antigen with lysosomal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…SMA) while being negative for S100 4 . Granular cell basal cell carcinoma has been well documented and shows the basal palisading found in its non‐granular counterpart while retaining positivity for some cytokeratins and Ber‐EP4 5–7 . Granular cell atypical fibroxanthoma has been described in chronically sun‐damaged skin of elderly patients and is negative for the S100 antigen 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In cutaneous sites, strong S100 positivity raises the possibility of melanocytic origin. Also, the coarse cytoplasmic granularity typical of GCT has been documented in neoplasms of various histogenetic lineages including melanocytic neoplasms 2–13 . The differential diagnosis therefore, of S100‐positive cutaneous lesions with granular cell morphology, includes both melanocytic neoplasms and cutaneous GCT.…”
mentioning
confidence: 99%